A novel spinning process for simultaneously producing two cone parts with big angle. (3rd October 2018) - Li, Ming; Xu, Yuanyi; Li, Heng; Wang, Hongji; Shi, Wenchao; Wu, Yucheng
ABSTRACT: A new spinning forming method for simultaneously producing two cone parts with big angle was developed. The novel process with three passes was generated. The 3D finite element (FE) model of cone parts was established using ABAQUS software. Based on the metal plastic forming principle and the characteristic of spinning, technical parameters including the angle of forming surface and the radial feed speed of the roller, the spindle speed and the friction coefficient were determined. Based on the secondary development of above FE model, the fittability of cone parts was obtained, which is of great significance for improving the performance of cone parts.